Association between Vitamin D Status, Oxidative Stress Biomarkers and Viral Load in Human Immunodeficiency Virus Type 1 Infection - Flauzino, Tamires; N.C. Simao, Andrea; R.D. de Almeida, Elaine; K. Morimoto, Helena; R. Oliveira, Sayonara; F. Alfieri, Daniela; T. Ueda, Luiz; Dichi, Isaias; M.V. Reiche, Edna (Current HIV Research, 2017)
Background: The role of vitamin D in the pathophysiology of human immunodeficiency virus type 1 (HIV-1) infection is still unclear. Objective: To evaluate the associations between vitamin D and immunological, virological, and oxidative stress biomarkers in individuals with human immunodeficiency virus type 1 (HIV-1) infection. Methods: The serum levels of 25 hydroxyvitamin D [25(OH)D] were determined in 314 HIV-1- infected individuals and 127 controls and the values ≥30 ng/mL defined a vitamin D sufficient (VDS) status, and <30 ng/mL defined the presence of hypovitaminosis D (HD). Oxidative stress was evaluated with plasma levels of lipid hydroperoxides, advanced oxidation protein products (AOPP), carbonyl protein, nitric oxide metabolites (NOx), total radical-trapping antioxidant parameter (TRAP), and sulfhydryl groups of proteins. Plasma HIV-1 viral load and CD4+/CD8+ T cells were quantified. Results: The 25(OH)D levels and vitamin D status did not differ between HIV-1-infected individuals and controls. Hydroperoxides and AOPP were higher (p<0.0001 and p=0.002, respectively), whereas TRAP, carbonyl protein, and NOx were lower in HIV-1-infected individuals than controls (p<0.0001). HIV-1-infected individuals with HD showed higher hydroperoxide levels than those with a VDS status (p=0.012) and controls (p=0.022), independent of ethnicity and antiretroviral therapy. A positive correlation between 25(OH)D ≥30 ng/mL and viral load was observed when expressed as the number of copies/mL (r=0.178, p=0.039), as well as log10 copies/mL (r=0.183, p=0.033). Conclusion: These results suggest the bimodal influence of vitamin D in the modulation of immune response in HIV-1 infection, considering its differential susceptibility to modulation of the various immune targets and pathways.
Keywords: HIV-1 infection